2016
DOI: 10.1117/1.jrs.10.046018
|View full text |Cite
|
Sign up to set email alerts
|

Method for estimating rice plant height without ground surface detection using laser scanner measurement

Abstract: , "Method for estimating rice plant height without ground surface detection using laser scanner measurement," J. Appl. Remote Sens. 10(4), 046018 (2016), doi: 10.1117/1.JRS.10.046018. Relative vertical distances (rD) were computed from the difference between the top and bottom positions of the rice plant. These correlated well with measured H, with slopes greater than 1.0. A greater number of stems in 2014 led to steeper slopes. Estimated H was more accurate when plant bottom positions were closer to the groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…Here, we assume that scanning angle effects can be ignored. As reported in our previous study, 28 the relative vertical distance (rD), computed directly from the laser data without considering the ground-surface level, was related to H and was insignificantly affected by the planting density. Therefore, under the practical scenario of this study, we normalize D not by H but by the respective rDs derived from the laser data at each observation time.…”
Section: Computation Of Relative Spatial Volume From the Observed Lassupporting
confidence: 68%
See 3 more Smart Citations
“…Here, we assume that scanning angle effects can be ignored. As reported in our previous study, 28 the relative vertical distance (rD), computed directly from the laser data without considering the ground-surface level, was related to H and was insignificantly affected by the planting density. Therefore, under the practical scenario of this study, we normalize D not by H but by the respective rDs derived from the laser data at each observation time.…”
Section: Computation Of Relative Spatial Volume From the Observed Lassupporting
confidence: 68%
“…In our previous study, we computed D of the scanning points by multiplying the observed range data by the cosine of the corresponding inclination angle. 28 Here, D denotes the position of the laser pulse on the rice canopy above the ground surface. Of course, the range of D depends on the observation date because H increases over time.…”
Section: Data Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…By establishing the estimation model, which is the function of feed amount and crop volume, they accurately calculated crop density. In order to acquire the rice density, Phan et al [18] put forward a method that divided the voxels of rice point-cloud data and calculated the spatial volume. As the spatial volume depends on the height of the rice and the numbers of plants, the rice density could be measured by inverse transformation after removing the influence of rice height.…”
Section: Introductionmentioning
confidence: 99%